Immediate effects and duration of a short and single application of transcutaneous auricular vagus nerve stimulation on P300 event related potential - Gurtubay, Iñaki G.; Perez-Rodriguez, Diego R.; Fernandez, Enrique; Librero-Lopez, Julian; Calvo, David; Bermejo, Pedro; Pinin-Osorio, Carolina; Lopez, Miguel (Frontiers in Neuroscience, 2023)
Transcutaneous auricular vagus nerve stimulation (taVNS) is a neuromodulatory technique that stimulates the auricular branch of the vagus nerve. The modulation of the locus coeruleus-norepinephrine (LC-NE) network is one of the potential working mechanisms of this method. Our aims were 1- to investigate if short and single applications of taVNS can modulate the P300 cognitive event-related potential (ERP) as an indirect marker that reflects NE brain activation under control of the LC, and 2- to evaluate the duration of these changes. 20 healthy volunteers executed an auditory oddball paradigm to obtain P300 and reaction time (RT) values. Then a 7 min active or sham taVNS period was initiated and simultaneously a new P300 paradigm was performed. We successively repeated the paradigm on 4 occasions with different time intervals up to 56 minutes after the stimulation onset. During active taVNS an immediate and significant effect of increasing the amplitude and reducing the latency of P300, as well as a shortening in the RT was observed. This effect was prolonged in time up to 28 min. The values then returned to pre-stimulation levels. Sham stimulation did not generate changes. Our results, demonstrate differential facilitating effects in a concrete time window after taVNS. Literature about the modulatory effect of taVNS over P300 ERP shows a wide spread of results. There is not a standardized system for taVNS and currently the great heterogeneity of stimulation approaches concerning targets and parameters, make it difficult to obtain conclusions about this relationship. Our study was designed optimizing several stimulation settings, such as a customized earbud stimulator, enlarged stimulating surface, simultaneous stimulation over the cymba and cavum conchae, a Delayed Biphasic Pulse Burst and current controlled stimulation that adjusted the output voltage and guaranteed the administration of a preset electrical dose. Under our stimulation conditions, targeting vagal nerve fibers via taVNS modulates the P300 in healthy participants. The optimal settings of modulatory function of taVNS on P300, and their interdependency is insufficiently studied in the literature, but our data provides several easily optimizable parameters, that will produce more robust results in future.